Cubic function and Alternating Series

Calculus Level 4

Let ( 0 x 1 ) (0 \leq x \leq 1) .

Let g ( x ) = x 3 + a x 2 + b x + c g(x) = x^3 + ax^2 + bx + c and f ( x ) = n = 1 ( 1 ) n + 1 x n n f(x) = \sum_{n = 1}^{\infty} (-1)^{n + 1} \dfrac{x^n}{n} , where f ( 0 ) = g ( 0 ) , f ( 1 ) = g ( 1 ) f(0) = g(0), f(1) = g(1) and 0 1 f ( x ) d x = 0 1 g ( x ) d x \displaystyle \int_{0}^{1} f(x) dx = \int_{0}^{1} g(x) dx .

Find the area of the region bounded by f f and g g on [ 0 , 1 2 ] [0,\dfrac{1}{2}] to eight decimal places.


The answer is 0.01393112.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
May 13, 2018

Let ( 0 x 1 ) (0 \leq x \leq 1) .

Let f ( x ) = n = 1 ( 1 ) n + 1 x n n f(x) = \sum_{n = 1}^{\infty} (-1)^{n + 1} \dfrac{x^n}{n} .

d d x ( f ( x ) ) = n = 1 ( 1 ) n + 1 x n 1 = 1 1 + x f ( x ) = 0 x 1 1 + x d x = ln ( 1 + x ) \implies \dfrac{d}{dx}(f(x)) = \sum_{n = 1}^{\infty} (-1)^{n + 1} x^{n - 1} = \dfrac{1}{1 + x} \implies f(x) = \int_{0}^{x} \dfrac{1}{1 + x} dx = \ln(1 + x) .

g ( 0 ) = f ( 0 ) = 0 c = 0 g(0) = f(0) = 0 \implies c = 0 and g ( 1 ) = f ( 1 ) = ln ( 2 ) a + b = ln ( 2 ) 1 g(1) = f(1) = \ln(2) \implies \boxed{a + b = \ln(2) - 1}

For 0 1 ln ( 1 + x ) d x \int_{0}^{1} \ln(1 + x) dx

0 1 ln ( 1 + x ) d x = ( x ln ( 1 + x ) + ln ( 1 + x ) x ) 0 1 = ( ( x + 1 ) ln ( x + 1 ) x ) 0 1 = 2 ln ( 2 ) 1 \int_{0}^{1} \ln(1 + x) dx = (x\ln(1 + x) + \ln(1 + x) - x)|_{0}^{1} = ((x + 1)\ln(x + 1) - x)|_{0}^{1} = 2\ln(2) - 1

2 ln ( 2 ) 1 = 0 1 g ( x ) d x = 0 1 x 3 + a x 2 + b x d x = ( x 4 4 + a x 3 3 + b x 2 2 ) 0 1 = 1 4 + a 3 + b 3 \implies 2\ln(2) - 1 = \int_{0}^{1} g(x) dx =\int_{0}^{1} x^3 + ax^2 + bx dx = (\dfrac{x^4}{4} + \dfrac{ax^3}{3} + \dfrac{bx^2}{2})|_{0}^{1} = \dfrac{1}{4} + \dfrac{a}{3} + \dfrac{b}{3} \implies

4 a + 6 b = 24 ln ( 2 ) 15 \boxed{4a + 6b = 24\ln(2) - 15}

a + b = ln ( 2 ) 1 \boxed{a + b = \ln(2) - 1}

b = 20 ln ( 2 ) 11 2 \implies b = \dfrac{20\ln(2) - 11}{2} and a = 9 2 ( 1 2 ln ( 2 ) ) a = \dfrac{9}{2}(1 - 2\ln(2)) \implies g ( x ) = x 3 + 9 2 ( 1 2 ln ( 2 ) ) x 2 + ( 20 ln ( 2 ) 11 2 ) x g(x) = x^3 + \dfrac{9}{2}(1 - 2\ln(2))x^2 + (\dfrac{20\ln(2) - 11}{2})x \implies

0 1 2 g ( x ) f ( x ) d x = x 4 + 3 2 ( 1 2 ln ( 2 ) ) x 3 + ( 20 ln ( 2 ) 11 4 ) x 2 0 1 2 ( ( x + 1 ) ln ( x + 1 ) x ) 0 1 2 ) = \int_{0}^{\frac{1}{2}} g(x) - f(x) dx = \dfrac{x}{4} + \dfrac{3}{2}(1 - 2\ln(2))x^3 + (\dfrac{20\ln(2) - 11}{4})x^2|_{0}^{\frac{1}{2}} - ((x + 1)\ln(x + 1) - x)|_{0}^{\frac{1}{2}}) =

56 ln ( 2 ) 31 64 + 1 2 3 2 ln ( 3 2 ) 0.01393112 \dfrac{56\ln(2) - 31}{64} + \dfrac{1}{2} - \dfrac{3}{2}\ln(\dfrac{3}{2}) \approx \boxed{0.01393112} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...